Immunotargets and Therapy for Systemic Lupus Erythematosus - Mok CC (ImmunoTargets and Therapy)
Chi Chiu Mok Department of Medicine and Geriatrics, Tuen Mun Hospital, Hong KongCorrespondence: Chi Chiu Mok, Department of Medicine & Geriatrics, Tuen Mun Hospital, Tsing Chung Koon Road, New Territories, Hong Kong, SAR, People’s Republic of China, Tel +85224685386, Fax +85224569100, Email ccmok2005@yahoo.comAbstract: The pathophysiology of systemic lupus erythematosus (SLE) is complex and involves most cell types of the innate and adaptive immune system. Impaired clearance of apoptotic bodies and self-antigens, dysregulated cytokine network and aberrated functions of the immune cells lead to overproduction of autoantibodies, activation of complements, immune complex deposition and tissue injury. Novel biological and newer generation immunosuppressive agents have been developed to target the B cells, T cells, T/B cell interaction, plasmacytoid dendritic cells and the cytokines. With the advances in the knowledge about the intracellular pathways, small molecules that inhibit the downstream signal transduction from surface receptors and intracellular protein degradation by the ubiquitin-proteasome system are being developed in the pipeline. This article summarizes the evidence of various immunotargets for the treatment of SLE. These novel agents target specific cellular mechanisms, and further works are necessary to stratify patients according to biomarkers to receive individualized therapies that could help maximize the clinical response. With the availability of more therapeutic choices, a combination approach to achieve synergistic effects while reducing adverse events by dosage reduction of individual drugs is being explored for SLE patients at risk of disease progression or refractory to conventional therapies.Keywords: target, immune, therapeutics, novel, biologics, small molecules, lupus